RELIGION AND POLITICS IN INDONESIA: A LITERATURE REVIEW - Surbakti, Ramlan (Jurnal Bestari, 1994)
Because religion increasingly play an important role in political life, the relationship between religion and politics is an important topic of investigation. A review of the secholarly literature shows that different aspects of the relationship between religion and politicts have been studied by many scholars. However, this review also concludes that the interrelationship between religious and political power has not been studied in Indonesia and is therefore a relevant topic of research.